1962
DOI: 10.1063/1.1728745
|View full text |Cite
|
Sign up to set email alerts
|

Noncoherent Switching in Permalloy Films

Abstract: This article is copyrighted as indicated in the article. Reuse of AIP content is subject to the terms at: http://scitation.aip.org/termsconditions. Downloaded to ] IP: 130.70.241.163 On: Tue, 23 Dec 2014 01:48:37 PLASMA POTENTIAL MEASUREMENTS 1399 ACKNOWLEDGMENTSThese experiments owe their origin to a suggestion by R. A. Dandl. The members of the DCX-l group who are responsible for the guccessful operation of the facility, which in tum is responsible for the completion of these experiments, are

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

1966
1966
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(20 citation statements)
references
References 27 publications
1
18
0
Order By: Relevance
“…A 180 ± magnetic reversal is initiated typically in one of two ways: either we apply a magnetic field so that the energy barrier to reversal remains finite and reversal occurs by thermally assisted hopping or we apply a large enough field so that reversal is energetically favored independent of thermal effects. In the latter case, the magnetic reversal proceeds with some nonequilibrium or "dynamic" relaxation time t n that has been measured to be on the order of nanoseconds or less in exchange coupled materials with uniform, uniaxial anisotropy [3][4][5][6]. Calculations using the Landau-Lifshitz-Gilbert (LLG) equation have yielded a value of t n in good agreement with the experimental results for the simple case of coherent rotation of the magnetization [4,6].…”
supporting
confidence: 53%
See 1 more Smart Citation
“…A 180 ± magnetic reversal is initiated typically in one of two ways: either we apply a magnetic field so that the energy barrier to reversal remains finite and reversal occurs by thermally assisted hopping or we apply a large enough field so that reversal is energetically favored independent of thermal effects. In the latter case, the magnetic reversal proceeds with some nonequilibrium or "dynamic" relaxation time t n that has been measured to be on the order of nanoseconds or less in exchange coupled materials with uniform, uniaxial anisotropy [3][4][5][6]. Calculations using the Landau-Lifshitz-Gilbert (LLG) equation have yielded a value of t n in good agreement with the experimental results for the simple case of coherent rotation of the magnetization [4,6].…”
supporting
confidence: 53%
“…In the latter case, the magnetic reversal proceeds with some nonequilibrium or "dynamic" relaxation time t n that has been measured to be on the order of nanoseconds or less in exchange coupled materials with uniform, uniaxial anisotropy [3][4][5][6]. Calculations using the Landau-Lifshitz-Gilbert (LLG) equation have yielded a value of t n in good agreement with the experimental results for the simple case of coherent rotation of the magnetization [4,6]. In the case of a finite energy barrier E B , reversal occurs with the scaled relaxation time given by the Arrhenius-Néel law, t th t 0 exp͑E B ͞k b T ͒, where t 0 is the average relaxation time in response to a thermal fluctuation [7].…”
mentioning
confidence: 99%
“…11,12 The existence of such loop structure in single isolated Permalloy films has been known for some time and they are usually associated with a clearly visible pinning point such as an inclusion. 13 The 360°wall loop structures can also exist despite an absence of obvious topological pinning sites in some magnetic layered systems. Repetition of the magnetization cycle showed that there was a strong tendency for rather similar complex domain structures to form in approximately the same places within the sample, which suggests that there were locations where 360°wall loop structures were significantly stabilized.…”
Section: B Lorentz Transmission Electron Microscopy Studiesmentioning
confidence: 99%
“…360DWs were first observed in unpatterned ferromagnetic single layers 12,13 and were later generated deliberately in patterned ferromagnetic rings and other structures consisting of single layers and multilayers, both experimentally and by modeling approaches. [14][15][16][17][18][19][20][21][22] Within a magnetic strip containing a densely-packed array of 180DWs, such as those proposed for racetrack memory devices, the generation of 360DWs may be expected as a result of attractions between 180DWs due to their stray fields.…”
mentioning
confidence: 99%